Business Analysis Of Waste Banks Connecting Perpres Number 6 In 2015 On Creative Economic Agency (Feasibility Study On KSM Ngudi Kamulyan In Semarang City) - Dwi Astutik; Septian Yudha Kusuma; Hani Krisnawati (FEB UNTAG Semarang, 2018)
Community effort in creating to increase the benefits of resources is one of the concepts of creative economy which is currently an important issue in Indonesia. Evidently the issuance of PERPRES No. 6 of 2015 concerning the Creative Economy Agency, needs to be encouraged, strengthened and promoted as an effort to increase national economic growth. The emergence of KSM Ngudi Kamulyan which is engaged in the processing of waste into various handicraft products, is concrete evidence in supporting the regulation. The business will certainly experience ups and downs, in 2005-2008 it was not operating because it suffered losses and was active again in late 2008 until now. Organizations that are profit motive must be oriented to the feasibility of business sustainability, so that a study of economic feasibility studies is needed. The study of the response of creative industries and the public regarding the strategic plan of the regulation is also an important part. This research was conducted using qualitative descriptive analysis tools. The results obtained that the management stated that the existence of this regulation created a great sense of optimism to develop the creativity of waste management into various handicraft products. This optimism is accompanied by a note that efforts are needed to educate the public, reformulate the scale of business that is feasible, the introduction of appropriate technology and the ease of access to various Deputies prepared by the government. Unfortunately most people actually feel pessimistic and are not sure that the existing deputies are able to support waste management into a creative industry. Based on the analysis of the feasibility study of the financial aspects of the development plan that is projected by the board, a payback period of 4 years 1 month > the duration of the required credit tenor (4 years) is obtained, NPV Rp. -2,813,268 (negative), IRR 10.91% < average credit interest rate (13.65%) and B / C 0.95 < 1. The results of the calculation show that economically the business development plan is on a projected by KSM Ngudi Kamulyan is not feasible.Keywords : creative economy, PP, NPV, IRR, B/C.